Guidelines for the management of Primary Aldosteronism - Gomez-Sanchez, Celso E. (2022)
Primary aldosteronism is the most common form of secondary hypertension and is present in 5-24% of patients with hypertension and is associated with a significant increase in cardiovascular, cerebrovascular and renal morbidity compared to primary hypertension. Diagnosis depends on the demonstration of an increase in the autonomous secretion of aldosterone in the presence of high salt intake and non-responsive to the renin-angiotensin system. The most common forms of primary aldosterone are an aldosterone-producing adenoma and bilateral idiopathic aldosteronism and less common are unilateral hyperplasia and aldosterone-producing carcinoma. The differential diagnosis is done using a CTscan and especially adrenal vein sampling. The treatment for an aldosterone-producing adenoma is laparoscopic surgery and medical treatment in bilateral aldosteronism with mineralocorticoid receptor antagonists (spironolactone or eplerenone).